Особенности рынка кейтеринговых услуг в России - Safronova E. O. (Научное сообщество студентов, 2016)
In article it is told about the concept of catering, about its origin and features of the Russian market of catering services
Keywords: история; особенности; рынок общественного питания; features; history; кейтеринг; кейтеринг в России; catering; catering in Russia; the market of public catering